2003
DOI: 10.1099/jmm.0.05349-0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the Tannerella forsythensis (Bacteroides forsythus) siaHI gene and purification of the sialidase enzyme

Abstract: Tannerella forsythensis (previously named Bacteroides forsythus) is a Gram-negative, anaerobic, fusiform bacterium that is a primary or secondary aetiological agent in periodontal disease in humans. T. forsythensis expresses several putative virulence factors, including a sialidase; however, there has been no molecular genetic characterization of this enzyme. A sialidase clone (pHI-1) was screened from a total of 455 recombinant clones of a genomic DNA library using the 29-(4-methylumbelliferyl)-AE-D-N-acetyln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…Further, the post-translational addition of carbohydrates to the gingipains is highly variable, thus implicating a role for multiple factors in this process. In this study, the VimA protein was also observed to interact with the b-lactamase and sialidase proteins,which are known to play a role in sugar metabolism (Ishikura et al, 2003;Smayevsky et al, 2001;Brook, 1989;Hedberg & Nord, 1996;Sechi et al, 2004). Although sialylation can be involved in protein maturation, its role, if any, in gingipain biogenesis is unknown.…”
Section: Discussionmentioning
confidence: 88%
“…Further, the post-translational addition of carbohydrates to the gingipains is highly variable, thus implicating a role for multiple factors in this process. In this study, the VimA protein was also observed to interact with the b-lactamase and sialidase proteins,which are known to play a role in sugar metabolism (Ishikura et al, 2003;Smayevsky et al, 2001;Brook, 1989;Hedberg & Nord, 1996;Sechi et al, 2004). Although sialylation can be involved in protein maturation, its role, if any, in gingipain biogenesis is unknown.…”
Section: Discussionmentioning
confidence: 88%
“…The previously described SiaHI protein of T. forsythia (19) does not account for all of the sialidase activity of this putative periodontal pathogen. This bacterium has an orthologue of B. fragilis NanH, TF0035 (renamed NanH), which has sialidase activity when expressed in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acids were eluted from the column by using a linear gradient of sodium acetate (20 to 150 mM over 40 min) in 100 mM sodium hydroxide at a flow rate of 1 ml/min. N-Acetylneuraminic acid and N-glycolylneuraminic acid concentrations in assays were determined by comparison of peak areas with those of the authentic sialic acids (Sigma) as standards over a concentration range of 0 to 50 M. (19), it is not apparent whether this alone is sufficient to account for all of the sialidase activity in this bacterium. Sialidase activity not directly attributable to SiaHI was observed upon nondenaturing gel electrophoresis of T. forsythia proteins (19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations